MULTIPLE USE OF DISPOSABLE INSULIN SYRINGES IN THE SAME PATIENT - Zarif, Mohammad (Journal of Ayub Medical College Abbottabad, 1988)
Disposal syringes have brought a revolution in the control of serious transmissible diseases by parenteral route for example serum hepatitis, where the carrier of E antigen has a transmission risk of 35%.1,2 Diabetes Mellitus is a lifelong disease and in a country like our insulin dependent poor diabetics find it expensive to use a fresh insulin syringe for every injection. The cost of treatment is the principal reason for failure of compliance in developing countries like ours. Considering the above facts, a trial was organized with the aim to use repeatedly a disposable insulin syringe and needle in the same patient.